Pengembangan Instrumen Penilaian Model Two-Tier Multiple Choice Question (TTMCQ) pada Materi Pancadharma - Mirrah Megha Singamurti (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
This study aimed to develop a Two Tier Multiple Choice Question Assessment instrument that is suitable for use in Pancadharma material and to find out the teachers and students’ responses to the instrument developed. This study was conducted using the RD method applying the steps from Borg and Gall. The locations of the study were at the State Junior High Schools 1 and 2 Keling in Jepara Regency. Data collection used questionnaires, test, interviews and documentation. The results of this study exhibited that the TTMCQ assessment instrument developed for the Pancadharma material had 92.22% of content validation; the reliability scores were 0.754 for first tier and 0.826 for two tier; the power of distinguishing questions was categorized into a good category with the percentage of 66.67% for the main questions, and 46.66% for the reason questions. The difficulty level test indicated that 40% of the multiple choice questions were easy and 53.33% of them were medium, and 60% of the reason questions were easy, and 33.33% of them were medium. The teachers and students’ responses to the TTMCQ instrument developed in the form of multiple-choice multiple-level questions were more complicated than those of regular multiple-choice questions; the form of the questions was good and neatly organized; and the form of the questions was more about children’s responsibility in terms of thinking and solving problems. Thus, the TTMCQ instrument that had been developed was included in the appropriate category to be used as an assessment instrument of the Pancadharma material.